2019
DOI: 10.1016/j.gene.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomal and Argonaute-bound microRNAs in preeclampsia

Abstract: Introduction: microRNAs (miRNAs) play important role in the regulation of placental development, and abnormal miRNA expression is associated with preeclampsia (PE). miRNAs are released from trophoblast cells to maternal blood flow, where they are highly stable, being encapsulated inside extracellular vesicles, like exosomes or bound to Argonaute proteins. In PE, placental dysfunction leads to aberrant extracellular miRNA secretion. hsa-miR-210 is a hypoxia-sensitive miRNA found to be upregulated in PE, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…The level of placenta has‐miR‐517c in PE group was upregulated but in exosome and Ago‐bound plasma no significant difference in the level of has‐miR‐517c between PE and normal group was detected. It was also shown that the level of has‐miR‐16 in placenta, exosome, and Ago‐bound plasma had no significant difference between two groups . Exosomal has‐miR‐210 may have impact in intracellular communication and etiology of PE disease and also release of Ago‐bound has‐miR‐210 could be the by‐product of cell death and several manifestations of PE diseases .…”
Section: Epigenetic Changes In Pementioning
confidence: 94%
See 3 more Smart Citations
“…The level of placenta has‐miR‐517c in PE group was upregulated but in exosome and Ago‐bound plasma no significant difference in the level of has‐miR‐517c between PE and normal group was detected. It was also shown that the level of has‐miR‐16 in placenta, exosome, and Ago‐bound plasma had no significant difference between two groups . Exosomal has‐miR‐210 may have impact in intracellular communication and etiology of PE disease and also release of Ago‐bound has‐miR‐210 could be the by‐product of cell death and several manifestations of PE diseases .…”
Section: Epigenetic Changes In Pementioning
confidence: 94%
“…Has‐miR‐210 is one of the main markers of hypoxic responses in endothelial and trophoblast cells . Biro et al have reported that the level of has‐miR‐210 in exosome, Ago‐bound plasma, and placental was significantly upregulated in PE compared with normal group. Has‐miR‐517c is part of the primate‐specific C19MC miRNA cluster and expressed in placenta .…”
Section: Epigenetic Changes In Pementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, miR-136, -494 and -495 in the EVs secreted by umbilical cord mesenchymal stem cells (UCMSCs) were also highly expressed in PE patients when compared to healthy controls. The expression of miR-210 was found to be higher in PE placenta when compared to normal placenta; coincidentally, hypoxic conditions induce a high level of miR-210 release via EVs (Biro et al 2019).…”
Section: Pre-eclampsiamentioning
confidence: 89%